2014
DOI: 10.1007/s00408-014-9675-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Comorbidities on Survival of Non-small Cells Lung Cancer Patients

Abstract: Our study shows the importance of cardiovascular disease in lung cancer. Diabetes, cerebrovascular disorders, and COPD also have a significant impact on survival of NSCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 23 publications
3
61
1
Order By: Relevance
“…Meta-analysis demonstrated that the presence of COPD was associated with worse clinical outcome of lung cancer 27 . Even though we and other group demonstrated that lung cancer-associated with COPD preferentially harbored somatic mutations in a few genes, the tumors from COPD and non-COPD patients exhibited highly concordant genomic alterations, which might not explain the differences in clinical outcomes between these two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis demonstrated that the presence of COPD was associated with worse clinical outcome of lung cancer 27 . Even though we and other group demonstrated that lung cancer-associated with COPD preferentially harbored somatic mutations in a few genes, the tumors from COPD and non-COPD patients exhibited highly concordant genomic alterations, which might not explain the differences in clinical outcomes between these two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidities occur frequently in patients with lung cancer . These comorbidities are prevalent and confer significant impacts on the prognosis . The most crucial comorbidity is COPD (chronic obstructive pulmonary disease), with a prevalence of 40% to 70% .…”
Section: Introductionmentioning
confidence: 99%
“…12 case‐control studies were conducted in Korea, Denmark, Japan, the United States and Spain . In terms of diagnosis of COPD, 4 studies used Spirometry, 3 studies used GOLD guideline, 2 studies used American Thoracic Society criteria or European Respiratory Society criteria, 1 studies used Spirometry and/or Computed tomography (CT), 1 studies used Medical record and 1 studies used doctor‐diagnosis …”
Section: Resultsmentioning
confidence: 99%